Inocência ferida: uma investigação acerca das violências que incidem sobre os corpos de bebês e crianças pequenas nas creches - Soares, Tainá de Melo (Universidade Federal de São Carlos, 2025)
This final undergraduate research project aims to address the complex issue of violence directed at the vulnerable bodies of infants and young children in daycare centers, its types and forms od manifestation, as well as the factors that contribute to its acceptance, normalization, and, in some cases, even encouragement in educational routines. The study was motivated by experiences and observations during academic training in Pedagogy, particularly in early childhood education internships, where punitive, negligent, and authoritarian practices were identified and often legitimized as educational strategies. A qualitative, bibliographic approach was adopted, based by authors who discuss discipline, power, and symbolic violence in school institutions. The theoretical framework included books, scientific articles, and official documents that guide early childhood education in Brazil. The results highlight the presence of subtle and everyday forms of violence in daycare centers, such as shouting, punishment, exclusion from play, negligence, and disregard for children's emotional and expressive needs. Such practices, often legitimized by authoritarian pedagogical discourses and the burden of teaching work, represent forms of disciplining that harm childhood and reproduce control structures. Furthermore, the findings also point to adult-centric culture, the physical and organizational structures of institutions, and the persistence of historically rooted violent practices as justifications for the violence committed in daycare centers. It is concluded that overcoming this scenario demands public policies that value critical teacher training, institutional environments that are welcoming and sensitive to the uniqueness of young children, as well as the urgent deconstruction of violent discourses that validate and naturalize power and discipline relations. The study reaffirms the importance of building pedagogical practices based on active listening, respect for childhood, and overcoming adult-centrism as possible paths toward truly humanized early childhood education.
Wounded Innocence: An investigation into the violence inflicted on the bodies of babies and young children in daycare centers
Keywords: Violência; Creche; Profissionais da Educação; Violence; Daycare Center; Educational Professionals; CIENCIAS HUMANAS::EDUCACAO